(untitled) (Journal of Hama University, 2022)
Patients with Hematologic Malignancies are immunosuppressed because they receive high doses of chemotherapy, which makes them susceptible to opportunistic infections, especially fungal infections, of which Aspergillus is one of the most important causative factors. This study aims to investigate the incidence of aspergillosis in patients with hematologic malignancies and to determine the types of these Aspergillus. This study was conducted on 100 patients with hematologic malignancies attending the Hematology Department in some hospitals in the city of Homs, during the period between December 2020 and September 2021. Sputum samples were collected from the patients and a direct microscopic examination was performed on them, and then cultured on Sabouraud dextrose agar medium (SDA), supplemented with chloramphenicol. The identity of the developing Aspergillus was determined based on the macroscopic and microscopic shape of its colonies. The incidence of aspergillosis among patients was 11%. Aspergillus flavus and Aspergillus niger were the most isolated of Aspergillus species. with 36.36% each, followed by Aspergillus fumigatus with 27.27%. We found a significant association between aspergillosis and smoking, malignant blood disease type, and neutrophil count, while we did not find a relationship between aspergillosis and the patient’s gender and age.